The effectof using reciprocal teachingtowards students’ reading ability of recount text inthe eighth grade of SMPN 1 Sine - S. Sukini; Nuri Ati Ningsih; Dwi Rosita Sari (English Teaching Journal : A Journal of English Literature, Language and Education, 2018)
The purpose of this research is to know the effects of Reciprocal Teaching toward students’s reading ability of recount text in the eighth grade of SMPN 1 Sine in the Schooling year of 2016/2017. Reciprocal Teaching has four strategies, such as; Predicting, Questioning, Clarifying and Summarizing. The method that is used by the researcher is Experimental Design. The researcher used two classes, the first class as control class and the other one is expeimental class. Each class consists of 20 students. They had different treatment. The control class is not treat by the Reciprocal Teaching but the experiment class treated Reciprocal Teaching. The researcher got the data by using pretest and postest for each class. The test is 50 items of multiple choices. The researcher used SPSS v23 to count the result of the data. The data analysis showed the significancy of the data. The mean score for experimental group has 49, 20. Then, the mean score for control group has 43, 25. Based on the two means, it can be considered that both of the groups are significantly different. The results of the sig. of the Lavene’s test for equality of variances show that it exceeds the level of tolerance p. value .05. The result of sig. is .095. It means that there is no significant different from the two groups and Ho can be rejected. The mean score for group which is treated by using Reciprocal Teaching has 79, 55. Then, the mean score for the group which is not treated by using Reciprocal Teaching has 73, 55. The results of post-test both of the groups show significantly different. The result of independent sample t-test shows the significantly different can be seen from the sig. 004 in t-test for equality of means. This result is lower than the p value .05 of significance tolerance. It can be concluded that Reciprocal Teaching Technique is effective toward students’ reading ability of recount text in the eighthgrade of SMPN 1 Sine.